The First all-Russian Congress with International Representatives “Bioethics and Human Rights” - E. V. Tarasyants (Московский журнал международного права, 2009)
The first all-Russian Congress on Bioethics with international representatives was held on 26-27 September 2008 in Kazan, Republic of Tatarstan, Russian Federation under the auspices of the UNESCO Moscow Office, Commission of Russian Federation on UNESCO Affairs, Government of Republic of Tatarstan, Commission of the Republic of Tatarstan on UNESCO affairs, the Russian Foundation for Basic Research. The first day of Congress was followed by the General Assembly of Forum of National Ethics Committees of the CIS member states. The discussions during the Congress concerned the most important and sensitive issues such as protection of human rights (patient’s rights) during biomedical research, work of ethics committees during procedure of approval of clinical trials, status of fetus, international cooperation in the field of human rights and bioethics (including cooperation within UNESCO and the Council of Europe).The most significant result of the event reflected in the Final Document of the Congress is the recognition of necessity for the Russian Federation to adhere to the Convention on Human Rights and Biomedicine of 1997, and to submit to the Russian Committee on Bioethics a proposal to estimate the necessity and expediency for Russia to ratify the Additional Protocols to this Convention, including the Protocol on Transplantation of Organs and Tissues of Human Origin, the Protocol on Biomedical Research, the Protocol on Genetic Testing for Health Purposes.